Medicinal Plants of the Mardan Region: Phytochemicals and Pharmacological Insights - Khan, Adnan; Shah, Faryal Naseem; Haqnawaz, Javeria; Khan, Ihlam; Bakhtiar, Aneesa; Din, Zaheerud (Indus Journal of Bioscience Research, 2025)
Medicinal plants have long been recognized as valuable sources of bioactive compounds with therapeutic potential. This review highlights nine medicinal plants from the Mardan region of Pakistan, emphasizing their phytochemical composition and reported pharmacological activities. Literature was collected from scientific databases and ethnobotanical surveys, with a focus on studies reporting bioactive compounds and experimental validation of traditional uses. The selected species were found to contain diverse classes of phytochemicals, including alkaloids, flavonoids, terpenoids, tannins, and saponins. These metabolites contribute to a wide spectrum of biological activities, particularly antimicrobial, anti-inflammatory, anticancer, and antidiabetic effects. Antimicrobial activity was the most consistently reported, while anticancer and metabolic disorder–related studies remain limited. The analysis underscores the therapeutic promise of local flora but also highlights research gaps, such as insufficient clinical validation and lack of mechanistic studies. Future investigations should prioritize compound isolation, mode-of-action studies, and sustainable utilization. Overall, the findings demonstrate that the medicinal plants of Mardan represent an underexplored reservoir for novel drug discovery and pharmacological innovation.